HUBUNGAN ANTARA TINGKAT STRES DENGAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS DI WILAYAH KERJA PUSKESMAS SUKOHARJO I KABUPATEN SUKOHARJO - Septian Adi Nugroho; Okti Sri Purwanti (Jurnal Berita Ilmu Keperawatan, 2010)
Background of the study. According to data World Health Organization ( WHO), Indonesia occupies sequence to the bigger 4 in number Diabetes mellitus patient in world after India, China, and United States. Diabetes mellitus known as a disease which caused by existence of chronical trouble especially at system carbohydrate metabolism, fat, as well as protein in body. This disease actually preventable, between it by the way of changing life pattern either so that protected from stres. Stress and Diabetes mellitus has a real tightly relationship especially at urban resident. indisposed Life pressure and life style hardly having an effect, added with progress of technology that is increasingly fast and various disease is being in suffering causes degradation of condition of someone causing triggers the happening of stress. Stress at Diabetes mellitus patient can cause trouble at blood sugar rate control. In the situation stress there will be improvement of excretion of hormone katekolamin, gkukagon, glucocorticoid, - endorphin and growth hormone. Purpose of this research is to know the relation of level of stress to blood sugar rate to Diabetes mellitus patient in work region of Puskesmas Sukoharjo I Kabupaten Sukoharjo. This research is analytic descriptive research that is menganlisis relation between level of stres with blood sugar rate. Research sample is 48 diabetes mellitus patients in work region of Puskesmas Sukoharjo with technique simple random sampling. Data processing technique applies analytical technique Product Moment. The Time and instrument Research doing in mei month of 2010 year. Instrumen this research is quetionaire stress (HRS) Holmes Rating Scale and glukotest. Conclusion. Based on the result of research and solution, hence the conclusion from this research are: (1) the level of stres at Diabetes mellitus patient in Wilayah Kerja Puskesmas Sukoharjo I most of weight, (2) the blood sugar rate to Diabetes mellitus patient in work region of Puskesmas Sukoharjo I most of bad, and (3) There is correlation between level of stres with blood sugar rate to Diabetes mellitus patient in work region Puskesmas Sukoharjo I with p-value is 0,022 and r-value is 0.438